The Effect of the Flipped Classroom Model to Improve Critical Thinking and Reading Comprehension for Fifth-Grade Students - Arifin Ahmad; Bachrudin Mustafa; Dadang Sunendar; Ipal Taupik Rahman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This paper is motivated by the condition of students who lack Literacy and Critical Reasoning in the learning process and learning outcomes that are still many under KKM because teachers are less familiar with several methods and have yet to use the Flipped Classroom Model. This study aims to improve Reading Comprehension and Critical Thinking using the Flipped Classroom model. This research was conducted in class V of SDN Cibabat Mandiri 1 Cimahi City. This study uses quantitative research methods with the Quasi Experiment Design model using observation, interview, pretest, posttest, and documentation assisted by SPSS 29.0 to calculate the data obtained. With a population of 74 students. The technique used is collecting data on this test method before and after treatment. A live question-and-answer technique was used to find out the test results from the study. After that, samples were taken for the Experimental class, namely the VA class with 37 students and the VB class as the control class with 37 students, so a total of 74 students. Based on the Hypothesis Test results, there is a viable data variant after treatment. The data collection techniques used were observation, interview, pretest, and posttest. The results showed a significant influence on the use of flipped classrooms to improve the reading comprehension and critical thinking skills of grade V students of SDN Cibabat Mandiri 1 Cimahi City. Based on the results of the independent sample T-test, Sig was obtained. (2-tailed) Alternatively, (Significance Two Side-p) of 0.001 > 0.05 means Ho is rejected, and Ha is accepted. This is supported by the average score of the experimental class of 81.16 and the control class of 72.64.